2008
DOI: 10.1097/jto.0b013e3181653d1b
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of the Epidermal Growth Factor Receptor with Cetuximab, an IgG1 Monoclonal Antibody, and Gefitinib, A Tyrosine Kinase Inhibitor, in Patients with Refractory Non-small Cell Lung Cancer (NSCLC): A Phase I Study

Abstract: Dual EGFR inhibition with cetuximab and gefitinib is feasible; the combination can be safely administered and may have modest activity in advanced/metastatic NSCLC. Cetuximab 250 mg/m(2) weekly IV and gefitinib 250 mg/d PO is the recommended phase II dose, although the potential for late-onset hypomagnesemia warrants close monitoring of patients receiving this combined dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 34 publications
(33 reference statements)
1
38
0
Order By: Relevance
“…Moreover, cetuximab, alone or with chemotherapy, has shown limited efficacy in EGFR-driven lung cancer (30,31). Phase I studies have shown that various combinations of EGFR-TKI and EGFR monoclonal antibodies are safe and tolerable in patients with non-small cell lung carcinoma (32)(33)(34)(35)(36). However, combined EGFR inhibition has not been prospectively studied in patients with acquired resistance to EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cetuximab, alone or with chemotherapy, has shown limited efficacy in EGFR-driven lung cancer (30,31). Phase I studies have shown that various combinations of EGFR-TKI and EGFR monoclonal antibodies are safe and tolerable in patients with non-small cell lung carcinoma (32)(33)(34)(35)(36). However, combined EGFR inhibition has not been prospectively studied in patients with acquired resistance to EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Dual EGFR inhibition has been shown to be feasible in phase 1 studies with a combination of cetuximab and erlotinib in patients with advanced solid malignancies or cetuximab and gefitinib in patients with refractory NSCLC [30,31]. Conventional doses of each agent (250 mg/m 2 cetuximab intravenously weekly; 150 mg erlotinib orally daily; 250 mg gefitinib orally daily) were achieved but cutaneous toxicity, generally grade 1/2, seemed to be more frequent.…”
Section: Dual Her1/egfr Inhibitionmentioning
confidence: 97%
“…The triple combination of cetuximab/erlotinib/bevacizumab has been investigated in a phase 1 study of patients with advanced solid tumors, but toxicity did not allow the administration of usual erlotinib doses [31]. The triple combination of imatinib (400 mg daily), erlotinib (150 mg daily), and bevacizumab (10 mg/kg every 2 weeks) was found to be a tolerable therapy in a phase 1/2 trial of patients with advanced renal cell cancer, and there were early indications of activity.…”
Section: Combination Of Egfr Tkis and Anti-vegf Monoclonal Antibodiesmentioning
confidence: 99%
“…Bortezomib which is the first drug of a new class of targeted drugs that are proteasome inhibitors may be also synergistic with cetuximab [88]. Despite the benefit in preclinical studies, association of cetuximab with TKI or bortezomid did not lead to objective response in phase II trials [88][89][90][91][92][93]. To the best of our knowledge, no phase III has yet started.…”
Section: Cetuximab and Other Targeted Therapiesmentioning
confidence: 99%